Enrolment in micro life and health insurance: Evidences from Sri Lanka - Mirko Bendig; Thankom Arun (Institute for the Study of Labor (IZA), 2011)
Microinsurance is an emerging concept protecting households from the potentially catastrophic expenditures associated with family related shocks. Therefore, this paper presents evidence on the determinants of insurance participation using probit models on household survey data from Sri Lanka, conditional on household's microfinance institution enrolment. Further, we employ multivariate probit regressions to analyse factors affecting the participation in different types of insurance. We find that the household's experience of a family related shock is positively associated with the participation in micro health insurance schemes under study. There is strong evidence that microinsurance has not yet succeeded in proportionately reaching the most vulnerable households. Notably, education of the household head is a strong determinant of microinsurance participation.
urn:nbn:de:101:1-201104084387
Keywords: G22; O16; R22; 330; microinsurance; household behaviour; Sri Lanka; Lebensversicherung; Krankenversicherung; Mikrofinanz; Konsumentenverhalten; Familie; Schock; Schätzung; Sri Lanka